2021
DOI: 10.3390/ijerph18052476
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Resistance Training on Circulating Irisin: Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Irisin seems to play an important role in several chronic diseases, however, the interactions between chronic training and irisin are still unclear. The purpose of this systematic review and meta-analysis was to examine the effect of chronic resistance training on circulating irisin in adults. Literature search was conducted in PubMed, Web of Science and EBSCOhost (Academic Search Complete) until December 2020. Randomized controlled trials researching irisin levels after a resistance training program for at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…The current findings are generally consistent with prior reviews [18,86,[91][92][93] in that the effects of physical exercise on blood irisin levels vary. Although prior reviews describe the positive effects of both acute and chronic (long-term) effects of physical exercise, they also point to mixed results and the overall lack of evidence [18].…”
Section: Agreements and Disagreements With Other Studies Or Reviewssupporting
confidence: 90%
See 1 more Smart Citation
“…The current findings are generally consistent with prior reviews [18,86,[91][92][93] in that the effects of physical exercise on blood irisin levels vary. Although prior reviews describe the positive effects of both acute and chronic (long-term) effects of physical exercise, they also point to mixed results and the overall lack of evidence [18].…”
Section: Agreements and Disagreements With Other Studies Or Reviewssupporting
confidence: 90%
“…Especially, the older adult female population would benefit from this protective effect as they are prone to osteoporosis. Cosio et al [86] and Morteza et al [87] also showed greater increases of circulating irisin in older adults after resistance training programs. It would also be worth investigating the effect of neuromuscular electrical stimulation (NMES; a passive type of exercise) protocols, such as in the study by Jandova et al [88], on circulating irisin, which could offer an alternative mode of exercising for people with difficulties maintaining a physically active life.…”
Section: Summary Of Main Results and Interpretationsmentioning
confidence: 91%
“…In humans, FNDC5 is predominantly expressed in muscle tissue, and its expression patterns establish a few primary predictors of circulating irisin, such as muscle mass and age (23). Therefore, increased muscle tissue due to a resistance training program could be a way to increase circulating irisin levels, and these observations are substantiated by studies showing an increase in circulating irisin levels after aerobic and resistance exercise sessions (24,25). Furthermore, lower circulating irisin levels in older people have been noted because human muscle tissue mass decreases annually after 50 years of age (26).…”
Section: Irisinmentioning
confidence: 95%
“…Irisin is a myokine, cleaved as a peptide hormone of 112 amino acids from fibronectin type III domain containing 5 in skeletal muscle and secreted during aerobic exercise[ 32 ]. Irisin is positively correlated with an active lifestyle and vigorous intensity physical activity[ 32 ]. Both aerobic and resistance exercise are associated with high irisin levels, especially in older age groups[ 32 ].…”
Section: Newer Perspectives On Exercise Protection In Covid-19mentioning
confidence: 99%
“…Irisin is positively correlated with an active lifestyle and vigorous intensity physical activity[ 32 ]. Both aerobic and resistance exercise are associated with high irisin levels, especially in older age groups[ 32 ]. Irisin is involved in muscle hypertrophy and controls energy levels in muscle, participates in glucose homeostasis and browning of white adipose tissue, and has been implicated in exercise-induced neuroprotection as it is highly expressed in the brain[ 33 , 34 ].…”
Section: Newer Perspectives On Exercise Protection In Covid-19mentioning
confidence: 99%